Rehabilitation of a Spark Erosion Prosthesis: A Clinical Report - Julie C. Berger, DDS, MS;1 and Carl F. Driscoll, DMD2 (Journal of Prosthodontics, 2006)
When complex prostheses are fabricated, it is expected that at some point maintenance will be necessary.